Advances in Crystal Growth Inhibition Technologies - Amjad, Zahid. (Springer US, 2002)
In this book, academic researchers and technologists will find important information on the interaction of polymeric and non-polymeric inhibitors with a variety of scale forming crystals such as calcium phosphates, calcium carbonate, calcium oxalates, barium sulfate, calcium pyrophosphates, and calcium phosphonates. Moreover, the book delivers information to plant managers and formulators who would like to broaden and deepen their knowledge about processes involved in precipitation of sparingly soluble salts and learn more about the inhibitory aspects of various commercially available materials. Furthermore, experienced researchers will obtain fruitful and inspiring ideas from the easily accessible information about overlapping research areas, which will promote discoveries of new inhibitors (synthetic and/or natural) for the currently unmet challenges.